2002
DOI: 10.1002/bdd.303
|View full text |Cite
|
Sign up to set email alerts
|

Complete bioavailability and lack of food‐effect on pharmacokinetics of gliclazide 30 mg modified release in healthy volunteers

Abstract: A new modified release (MR) formulation containing 30 mg of gliclazide was developed to obtain a better predictable release of the active principle and to allow once-daily dosing regimen. An absolute bioavailability study was carried out to characterise the performance of the new formulation and the food-effect was also investigated in a separate study. Both studies were single dose, randomised, open label, two way cross over studies with a wash out period between doses. For the bioavailability study, each vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
39
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 10 publications
10
39
1
Order By: Relevance
“…Thus, it suggests a possible excipient effect on the solubility and dissolution rate of GLZ MR tablets, especially in acidic media. In addition, this observation is in agreement with reports from Harrower 8) and Delrat et al 9) that suggested that the dissolution of GLZ MR tablets is controlled by the formulation. This information was an important guide for the composition of the dissolution pH steps in our study.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Thus, it suggests a possible excipient effect on the solubility and dissolution rate of GLZ MR tablets, especially in acidic media. In addition, this observation is in agreement with reports from Harrower 8) and Delrat et al 9) that suggested that the dissolution of GLZ MR tablets is controlled by the formulation. This information was an important guide for the composition of the dissolution pH steps in our study.…”
Section: Resultssupporting
confidence: 93%
“…33) However, the MR tablets of the GLZ were formulated with a hydrophilic matrix to obtain a more consistent and less pH-dependent release. 8,9) Dissolution Studies Using USP Apparatuses 1 and 2 To date, a single official dissolution method for GLZ is described for IR tablets in the British Pharmacopoeia. 30) The method recommends the use of USP2 at 100 rpm and 900 mL of PBS (pH 7.4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations